OʻZBEK SHEVALARI TARKIBIDAGI ETNOGRAFIZMLARNING SOHALARARO BOGʻLIQLIGI - Nurjanov, O. (SCIENCE and SOCIETY, 2021)
This article describes the inter-diciplinary interdependence, diversity, etymological and semantic nature of the Uzbek dialects in Karakalpakstan in terms of their derivative bases. In particular, special attention is paid to the names of ceremonies associated with the profession, the terms used to describe various celebrations and holidays, folk sayings and proverbs associated with the names of ceremonies, ceremonial names based on myths, archaism, historical names.